(untitled) - Ruggiero Sardaro (Aestimum, 2017)
In recent years, the cliffs along the coastal stretch of Melendugno are being interested by coastal erosion. For its environmental, landscape and tourist value, the local authorities are planning several actions to be implemented in the short, medium and long term as part of one of the five regional projects included in the new Territorial Landscape Plan of Apulia. The paper aims to verify the effective interest of residents and tourists in the province of Lecce towards the renovation and upgrading projects for the cliffs of Melendugno through the choice experiment (CE). Such an approach could also define economic and fiscal incentives, as well as improve measures in order to promote bottom-up initiatives, with positive effects on the governance of the shores of Salento.